UJI Tarik KOMPOSIT KARBON DENGAN MATRIX POLYPROYLENE DENGAN PARAMETER SUHU KERJA 600℃ DENGAN MEDIA TEKAN LOGAM DAN KERAMIK - Mohammad Pandji Nugraha; Ilham Fahira Minan Nurrohman; Haris Ardianto; Hery Setiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Right now the distribution of polypropylene in the environment has become more and more so that it can pollute the environment. Thus polypropylene waste can be converted into a composite matrix. In this study, the manufacture of composites from recycled polypropylene was carried out, to be further combined with carbon fiber. After that, tensile testing is carried out to find out the mechanical properties. As a variation, there are differences in press media, namely using metal and ceramics. This research method is carried out experimentally, where when polypropylene waste has been softened using a heat gun at a temperature of 600 °C, it is emphasized using aluminum metal and ceramics so that polypropylene can be solid. Then for the dimensions of its manufacture according to ASTM D 638 for recycled polypropylene and ASTM D3039 for recycled polypropylene matrix carbon fiber composites. From the tensile test results for ASTM D638, specimens with suppression treatment using metal press media have an average maximum tensile strength of 5.40 MPa. As for specimens with ceramic press media has an average value of 6.32 MPa. Tensile testing on recycled polypropylene matrix carbon fiber composite specimens showed tensile strength with a value of 7.53 MPa for the treatment of metal press media and for ceramic press media its strength value of 10.66 MPa. Thus ceramic press media in the polypropylene composite manufacturing process is better than metal press media